IL-6: Sinalização na Hipertrofia Muscular e efeitos Metabólicos Sistêmicos - Costa, Eduardo Militz da (2022)
The myokines are substances produced in skeletal muscle by muscle contraction induced by strengthening exercise. They have the ability to act locally on skeletal muscle itself and also in other organs and body tissues. In this review, we discuss relevant aspects presented in scientificliterature with a high degree of evidence signalling Interleukin - 6 (IL-6) in muscle hypertrophy induced by strenght training exercises, and also the action arising from its release by skeletal muscle in the bloodstream, exerting effects on other organs and tissues, demonstrating that it has an important role in the interaction of immunoneuroendocrine system and pro and anti-inflammatory effects in the human body.